1994
DOI: 10.1021/bi00197a023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Arabinosylcytosine-Substituted DNA on DNA/RNA Hybrid Stability and Transcription by T7 RNA Polymerase

Abstract: Cytosine arabinoside (araC) is a potent antileukemic agent which interferes with DNA replication both as a dNTP competitive inhibitor as well as after its misincorporation into DNA. We previously developed a chemical methodology for the synthesis of DNA oligomers containing araC which allowed us to study its site specific effects on duplex stability and chemical reactivity [Beardsley, G. P., Mikita, T., Klaus, M., & Nussbaum, A. (1988) Nucleic Acids Res. 16, 9165], as well as its effects on DNA ligase and DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 63 publications
1
23
0
Order By: Relevance
“…Cytosine arabinoside substitutions in the central promoter region for phage T7 RNA polymerase did not modify polymerase binding, initiation, or transcriptional output (Mikita and Beardsley, 1994). However, phage RNA polymerases do not rely on the formation of a multiprotein initiation complex involving TBP but rather are sequence-dependent.…”
Section: Discussionmentioning
confidence: 87%
“…Cytosine arabinoside substitutions in the central promoter region for phage T7 RNA polymerase did not modify polymerase binding, initiation, or transcriptional output (Mikita and Beardsley, 1994). However, phage RNA polymerases do not rely on the formation of a multiprotein initiation complex involving TBP but rather are sequence-dependent.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have investigated the effect of several types of lesions on transcription elongation by T7 RNAP. Psoralen monoadducts and diadducts (25), benzo(a)pyrene (26,27), benzo(c)phenanthrene (28), tetrahydrofuran, acetylaminofluorene, and aminofluorene (29), and thymine glycol (30,31) block the elongating T7 RNAP when present in the transcribed strand, whereas aminofluorene (29) and cytosine arabinose do not block it (32).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, preinitiation complexes were formed by incubating rat liver protein fractions D (2 g, containing TFIID and TFIIH), B (1 g, TFIIF/TFIIE), recombinant rat TFIIB (3 ng), and rat liver RNAP II (0.5 g) at 28°C for 30 min. 20 M ATP and UTP and 40 Ci of [␣- 32 P]CTP (800 Ci/mmol) were added to the reaction for the labeling of nascent transcripts. Transcription was synchronized as all transcribing polymerases paused at position 15, at which the first GTP was required for further elongation.…”
Section: Methodsmentioning
confidence: 99%
“…The A-like form is preferable for RNA-DNA hybrid duplexes [32,33] (and for some short duplexes which contains the ribonucleotide insertion [34]), hence the reverse B ~ A transition within the binding channel should have a lower energetic barrier in these cases. Mikita and Beardsley [35,36] have shown that DNA replication can be arrested by structural lesion of arabinosylcytosine in. the template DNA strand.…”
Section: Crawling Dnamentioning
confidence: 99%
“…Structural studies on Bform DNA all indicate that the perturbations introduced by araC are slight to moderate in their effect, particularly compared to those changes introduced by many of the more bulky modifications of the DNA bases which grossly disturb duplex structure and stability. However, its inhibitory effects on DNA polymerase can be equal to or greater than some of these more aggressive structural lesions [36]. On the other hand, a molecular modeling study showed that strong steric clashes occurred when araC-G base pairs were built into an A-form helix environment [37].…”
Section: Crawling Dnamentioning
confidence: 99%